Restraining patients in acute care hospitals—A qualitative study on the experiences of healthcare staff - Sandra Siegrist‐Dreier; Isabelle Barbezat; Silvia Thomann; Dirk Richter; Sabine Hahn; Kai‐Uwe Schmitt (Nursing Open, 2022)
Abstract Aim The focus was to explore the perceptions and experiences of healthcare workers with respect to the use of restraints in acute care hospitals. Design The study followed a qualitative design. Methods Three topic‐based focus group interviews were conducted, involving 19 participants from the fields of nursing, physical therapy and medicine. For data collection and analysis, the method of mapping techniques for rapid qualitative data analysis was used. After discussing and validating the individual mind maps, all data were condensed to identify the key findings. Results Participants described restraints as safety measures for the patients. The implementation of most restraints was led by nurses. The use of restraints differed significantly, even in the interprofessional team. Attitudes and experiences were the main determinants for restraint use. Nurses asked for more discussion about restraints in the team, for more support at an interprofessional level and for better guidelines to help with the decision‐making process.